Decyzje coacha a zmiany sprawności działania gracza - Seweryniak, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper presents preliminary results of the researches concerning the coaching process in men's senior volleyball team. The goal is to verify empirically the new directions of coach and team interactions to regulate player's efficiency. Theoretical fundamental of the research is the conception of coaching in sport teams by Panfil [2004a]. It assumes that creating and using the synergy effects and regulating the individual activity influences team efficiency. Probably this influence is as strong as influence of player's individual skills. The main method used in the research was the sport project by Łasiński and Panfil [2004]. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 229-242